Promoción y prevención para el cuidado integral de la salud en el viejo: una nueva propuesta curricular. Facultad de enfermería. Universidad de Antioquia 1997. (1998)
ABSTRACT: The purpose of this new curriculum proposal is to favor the culture of promotion and prevention in the nursing community of the University of Antioquia in order to be used in the health service institutions and collective subjects of health care. This proposal is presented taking into consideration an integral approach of health and care in elderly by means of teaching-assistance integrating programs. The development of this education proposal starts from placing the elderly within the social, political, cultural, education, and health contexts, which allows the identification of solving problems and needs by multidisciplinary work projects in order to contribute to see and live the getting-old process as a part of the human vital process. It is basic for old people to build their life project with the meaningful support of people surrounding them as well as society. Thematic subnuclei are identified to allow the intervention of the problems and their priority. Rather than gathering courses, it is question of integrating different disciplines, creating living-together spaces, and scenarios of socialization (home and family) to contribute knowledge to the study, interpretation, explanation, and solution of problems. The projects for the human and social development of elderly should answer the needs to educate human resources in health and the social demands in order to have a truly changing education project.